2017
DOI: 10.1016/j.eja.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Yield, growth and grain nitrogen response to elevated CO2 in six lentil (Lens culinaris) cultivars grown under Free Air CO2 Enrichment (FACE) in a semi-arid environment

Abstract: Yield, growth and grain nitrogen response to elevated CO2 in six lentil (Lens culinaris) cultivars grown under Free Air CO2 Enrichment (FACE) in a semi-arid environment." European

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 42 publications
5
39
0
Order By: Relevance
“…Consistent with previous results on wheat from the same site (Houshmandfar et al, ; Tausz‐Posch, Seneweera, Norton, Fitzgerald, & Tausz, ), e[CO 2 ] stimulated net assimilation rates (A sat ) and biomass of lentil in our study (by 25% and 30%). Stimulation of grain yield by e[CO 2 ] was increased more in the high rainfall season (63%) than in the dry season (18%), in line with previous results on wheat and lentil in the same experimental facility (Bourgault et al, ; Fitzgerald et al, ; Houshmandfar et al, ; O'Leary et al, ), but in contrast to a long‐held paradigm that the CO 2 fertilization effect is greater under drier than wetter conditions (Kimball, ; Leakey, Bishop, & Ainsworth, ; McGrath & Lobell, ). That paradigm was challenged by a recent meta‐analysis (van der Kooi et al, ) and also by long‐term results from a FACE site in a high rainfall agroecosystem, demonstrating that severe drought diminished yield stimulation by e[CO 2 ] to zero (Gray et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Consistent with previous results on wheat from the same site (Houshmandfar et al, ; Tausz‐Posch, Seneweera, Norton, Fitzgerald, & Tausz, ), e[CO 2 ] stimulated net assimilation rates (A sat ) and biomass of lentil in our study (by 25% and 30%). Stimulation of grain yield by e[CO 2 ] was increased more in the high rainfall season (63%) than in the dry season (18%), in line with previous results on wheat and lentil in the same experimental facility (Bourgault et al, ; Fitzgerald et al, ; Houshmandfar et al, ; O'Leary et al, ), but in contrast to a long‐held paradigm that the CO 2 fertilization effect is greater under drier than wetter conditions (Kimball, ; Leakey, Bishop, & Ainsworth, ; McGrath & Lobell, ). That paradigm was challenged by a recent meta‐analysis (van der Kooi et al, ) and also by long‐term results from a FACE site in a high rainfall agroecosystem, demonstrating that severe drought diminished yield stimulation by e[CO 2 ] to zero (Gray et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…In legumes, the known decrease in grain [N] under e[CO 2 ] is less prevalent than in non‐legume crops (Myers et al, ), and we found that e[CO 2 ] decreased grain [N] by 4%, but only in the dry season. Decreases in grain [N] under e[CO 2 ] in a low rainfall environment were previously observed in lentil and field pea (Bourgault et al, ; Bourgault et al, ). In the high rainfall season, stimulation of N 2 fixation by e[CO 2 ] was apparently sufficient to maintain grain [N] with higher yield, similar to reports in soybean in high rainfall agroecosystems (Gray et al, ) and supported by the positive correlation between grain [N] and N deposition to grain from fixation (Figure ).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations